Hubungan pola menstruasi dengan kejadian anemia pada remaja putri - Trianingsih, Indah; Nurlaila, Nurlaila; Ningsih, Estu Ayu; Ayu, Resti (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Anemia is a serious public health problem, especially among adolescent girls. Adolescent girls are susceptible to anemia due to iron loss during menstruation. Menstrual patterns, including cycle regularity and duration, are thought to contribute to the incidence of anemia when they are abnormal. Purpose: To determine the relationship between menstrual patterns (cycle and duration) and the incidence of anemia in adolescent girls at Belalau 1 Senior High School, West Lampung. Method: This quantitative study used a cross-sectional design. A sample of 96 10th-grade adolescent girls was selected using a purposive sampling technique. Data were collected using a questionnaire and hemoglobin levels were measured using the Easy-Touch GCHB device. Data were analyzed univariately and bivariately using the Chi-Square test. Results: Statistical tests showed a significant relationship between the menstrual cycle and the incidence of anemia (p-value = 0.000; OR = 121.000), as well as a significant relationship between menstrual duration and the incidence of anemia (p-value = 0.000; OR = 56.533). Conclusion: There is a significant relationship between menstrual patterns (cycle and duration) and the incidence of anemia in adolescent girls.   Keywords: Adolescent Girls; Anemia, Menstrual Cycle; Menstrual Duration.   Pendahuluan: Anemia merupakan masalah kesehatan masyarakat yang serius, terutama pada remaja putri. Remaja putri rentan mengalami anemia karena kehilangan zat besi selama menstruasi. Pola menstruasi, termasuk keteraturan siklus dan lamanya menstruasi, diduga berkontribusi terhadap kejadian anemia ketika berada dalam kondisi yang tidak normal. Tujuan: Untuk mengetahui hubungan antara pola menstruasi (siklus dan lama menstruasi) dengan kejadian anemia pada remaja putri di SMA Negeri 1 Belalau Lampung Barat. Metode: Penelitian kuantitatif dengan desain cross- sectional yang dilakukan pada populasi sebanyak 125 dengan jumlah sampel sebanyak 96 orang remaja putri kelas X yang diambil menggunakan teknik purposive sampling. Data dikumpulkan menggunakan kuesioner dan pemeriksaan kadar hemoglobin menggunakan alat easy-touch GCHB . Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square. Hasil: Uji statistik menunjukkan terdapat hubungan yang signifikan antara siklus menstruasi dengan kejadian anemia (p-value = 0.000; OR = 121,000) serta terdapat hubungan yang signifikan antara lama menstruasi dengan kejadian anemia (p-value = 0,000; OR = 56,533). Simpulan: Terdapat hubungan yang signifikan antara pola menstruasi (siklus dan lama menstruasi) dengan kejadian anemia pada remaja putri.   Kata Kunci: Anemia,Siklus Menstruasi; Lama Menstruasi; Remaja Putri.